Value Co-Creation and Sustainability Communication: A Case Study of Lyfe With Less’ Instagram and Telegram - Snezana Swasti Brodjonegoro (Ikatan Sarjana Komunikasi Indonesia, 2023)
Globally, the term sustainability has been widely used since its first inception back in the 1990s. However, the term itself has only been popularly used in Indonesia for the past half-decade, following the initiation of the Sustainable Development Goals by the UN, which Indonesia supported. Since then, there have been numerous sustainability initiatives by civil communities that are based online. These communities somewhat became the ‘spearheads’ of sustainable consumption communication in Indonesia, educating netizens about various aspects of sustainable consumption, through various platforms – including Instagram and Telegram. This paper aims to analyze how followers and group-members co-create value related to sustainable consumption and lifestyle across the two communication platforms of a sustainable lifestyle online community: Lyfewithless. This paper employs qualitative approach, using value co-creation concept to understand the interaction and communication pattern on both Instagram & Telegram, and communication about/of sustainability as a macro lens to situate this case in the growing body of sustainability communication. Through analyzing the interaction on both platforms during the period of February-May 2022 and February-May 2023, this study shows that the Instagram account & Telegram group of Lyfewithless have slightly different value co-creation dynamics and levels, but complement each other to co-create value among its members and followers in building and rebuilding understanding about sustainable consumption. Furthermore, this study proposes that to achieve its intended impact, organizations must conduct both communication aboutsustainability and communication of sustainability. This study contributes to the sustainable consumption communication literature and supports the notion that civil communities hold important role in educating more people to adapt a more sustainable consumption behavior in the Indonesian context.